A semianalytical solution of the modified two‐dimensional diffusive root growth model. Issue 4 (17th May 2021) - Wang, Jun; Huang, Guanhua; Zhan, Hongbin; Mohanty, Binayak; Li, Jiusheng; Zotarelli, Lincoln
Abstract: Accurate estimation of the temporal and spatial root water uptake patterns in root zone is needed for an improved understanding of water and chemical transport dynamics in vadose zone. Rooting system is of great importance to describe the plant root water uptake directly. In this study, the diffusive root growth model was coupled with the Environmental Policy Integrated Climate (EPIC) crop growth model through changing the boundary condition, and a new semianalytical solution of the modified root diffusive model was derived considering the dynamic root length density distribution simulated by the EPIC crop growth model. To test the modified root growth model, the field‐measured data of maize ( Zea mays L.) and tomato ( Solanum lycopersicum L.) root length density distribution were used for parameter optimization. A MATLAB program was developed by coupling the modified root diffusive model with the genetic algorithm to facilitate the parameters optimization. Results showed that the simulated root length density distribution at different times was in a good agreement with the observed values. The RMSE and bias values ranged from 0.22 to 0.25 cm cm –3 and from −3.0 to 24.5%, respectively. The modified diffusive root growth model can therefore be used to simulate the two‐dimensional root growth during the crop growing period. Core Ideas: A novel diffusive root growth model was developed by coupling the EPIC crop growth model. A semianalytical solution of the modified diffusive root growth model was derived. The modified root growth model was tested using field experimental data of maize and tomato.